2019
DOI: 10.1021/acs.jpcc.8b10573
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Lanthanide-Doped Bismuth Vanadates: A Systematic Study by X-ray Photoelectron and Optical Spectroscopies

Abstract: Monoclinic BiVO4 has emerged in recent years as one of the most promising materials for photocatalytic evolution of oxygen under solar irradiation. However, it is in itself unable to phototcatalyze reduction of water to hydrogen due to the placement of the conduction band edge below the potential required for H2O/H2 reduction. As a consequence, BiVO4 only finds application in a hybrid system. Very recently, tetragonal lanthanide-doped BiVO4 powders have been shown to be able to both reduce and to oxidize water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The optical spectra of PrInO 3 , NdInO 3 , and SmInO 3 are considerably more complicated than that of LaInO 3 , with sharp peaks associated with localized 4f → 4f transitions to the low energy of the interband onsets. It is beyond the scope of the current paper to discuss assignment of this structure in detail, but in general terms, the 4f → 4f bands are very similar to those for the simple Ln 2 O 3 oxides or more complex doped materials such as the Bi 0.5 Ln 0.5 VO 4 vanadates …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The optical spectra of PrInO 3 , NdInO 3 , and SmInO 3 are considerably more complicated than that of LaInO 3 , with sharp peaks associated with localized 4f → 4f transitions to the low energy of the interband onsets. It is beyond the scope of the current paper to discuss assignment of this structure in detail, but in general terms, the 4f → 4f bands are very similar to those for the simple Ln 2 O 3 oxides or more complex doped materials such as the Bi 0.5 Ln 0.5 VO 4 vanadates …”
Section: Resultsmentioning
confidence: 85%
“…It is beyond the scope of the current paper to discuss assignment of this structure in detail, but in general terms, the 4f → 4f bands are very similar to those for the simple Ln 2 O 3 oxides or more complex doped materials such as the Bi 0.5 Ln 0.5 VO 4 vanadates. 66 The band structure calculations show that the band gaps for all four perovskites are either direct (LaInO 3 and NdInO 3 ) or that the energy difference between a lower energy indirect gap and the direct gap is so small (<0.01 eV) as to be negligible (PrInO 3 and SmInO 3 ). It is therefore appropriate to estimate the position of the interband absorption onset by plotting (F(R)hν) 2 against photon energy hν.…”
Section: Resultsmentioning
confidence: 95%
“…The predominant peak with a bump on its lower-binding-energy side, ranging from 2.5 eV to 12.5 eV, is the valence band (VB). The strongest splitting peaks located at ~9.0 eV and ~7.8 eV, in the middle of the VB, should be assigned to Lu 4 f 5/2 and 4 f 7/2 doublets [ 17 ]. Meanwhile, the Gd 4 f state presents as an asymmetric peak with much lower intensity located at ~8.2 eV, which is overlapped with the Lu 4 f doublet and a bump (broad and very low intensity) of the hybridized states between the bonding O 2 p and V 3 d .…”
Section: Resultsmentioning
confidence: 99%
“…In order to further expand the optical applications of REVO 4 -series materials, the influence of mixed-crystal hosts on the luminescence properties has also been explored. For example, Robinson et al proved that Bi 1− x Dy x VO 4 showed broader XRD peaks compared to DyVO 4 , and a progressive decrease in the bandgap with the increase in Bi concentration and crystal field effects should not be negligible for the 4 f -4 f transitions [ 17 ]. Kang et al confirmed that the adjustment of the cation fractions could tune the excitation tail and emission band maximum of Bi 3+ ions through bandgap modulation in the (Y,Sc)VO 4 host [ 18 ].…”
Section: Introductionmentioning
confidence: 99%